Genetic markers in carcinoma of the prostate - Dimopoulos, M.-A.; Germenis, A.; Savides, P.; Karayanis, A.; Fertakis, A. (European Urology, 1984)
The distribution of phenotypes and gene frequencies of the third component of complement (C3), group-specific component (Gc), haptoglobin (Hp) and transferrin (Tf) were studied in 115 patients with carcinoma of the prostate. The statistical analysis of our findings in comparison to the frequency of these genes in a control group of 155 patients with benign prostatic hyperplasia does not reveal any correlation between the distribution of the Hp and Tf phenotypes and the disease. On the contrary, a statistically significant association was found between carcinoma of prostate and C3(F) and Gc2 genes. The relative risk incidence of this malignancy is 1.56 and 1.81, respectively, for the carriers of these genes suffering from benign prostate hyperplasia.